Peptone and tomato extract induced early stage of embryo development of Dendrobium phalaenopsis Orchid - Nintya Setiari; Aziz Purwantoro; Sukarti Moeljopawiro; Endang Semiarti (Universitas Gadjah Mada, 2016)
Germination and growth of orchid seeds can be accelerated by the addition of organic supplement and plant extract in culture medium. The objective of this study was to determine the effect of peptone and tomato extract on early stage of embryo development of Dendrobium phalaenopsis orchids. Orchid seeds were sown on NP and VW medium with addition of 10% of CW (NPCW and VWCW). Five weeks after seed germination, about 58.03% seed germination was observed on VWCW medium, and only 37.45% seed germination on NPCW. Tomato extract and peptone were added in VWCW, resulting VWCWTP medium. After 4-8 weeks on VWCWTP, 94.42% seeds was germinated into plantlet, but only 67.30% germinated seeds on VWCW. To get optimal growth and development of D. phalaenopsis orchids embryos in the in vitro condition, supplement of 100 ml.L-1 coconut water, 100 mg.L-1 tomato extract and 2 mg.L-1 peptone into VW basic medium is required.